2021
DOI: 10.1167/iovs.62.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS Induced Lysosomal Dysfunction and Autophagy Impairment in an Animal Model of Congenital Hereditary Endothelial Dystrophy

Abstract: Purpose The Slc4a11 knock out (KO) mouse model recapitulates the human disease phenotype associated with congenital hereditary endothelial dystrophy (CHED). Increased mitochondrial reactive oxygen species (ROS) in the Slc4a11 KO mouse model is a major cause of edema and endothelial cell loss. Here, we asked if autophagy was activated by ROS in the KO mice. Methods Immortalized cell lines and mouse corneal endothelia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Oxidative stress is likely the cause of the altered gene expression and paracellular permeability since quenching ROS can reduce corneal edema 6,29 . Consistent with this notion, we found that reintroduction of Slc4a11 reduces mitochondrial superoxide levels within the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is likely the cause of the altered gene expression and paracellular permeability since quenching ROS can reduce corneal edema 6,29 . Consistent with this notion, we found that reintroduction of Slc4a11 reduces mitochondrial superoxide levels within the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the KO phenotype recapitulates CHED and indicates that the loss of SLC4A11 function is sufficient to cause endothelial dystrophy. Interestingly, oxidative stress attributable to the loss of SLC4A11 causes lysosomal and autophagy dysfunction [ 47 ], which could also be a consequence of ER stress. As described below in “SLC4A11 is a Mitochondrial Uncoupler”, the major source of oxidative stress in the SLC4A11 KO is from mitochondrial dysfunction.…”
Section: Slc4a11 Knock-out Modelsmentioning
confidence: 99%
“…In turn, this could produce ER stress and protein misfolding. If performed early, before there is significant cell loss and dysfunction, the mouse CHED model can be partially reversed by the delivery of the wild-type gene [ 48 ], or the systemic delivery of the antioxidant MitoQ that targets mitochondrial superoxide [ 47 ].…”
Section: Slc4a11 Knock-out Modelsmentioning
confidence: 99%
See 2 more Smart Citations